(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The forests of Polylepis (queñoales) is one of the most important Andean forest ecosystems and with the greatest impact due to human activities. The objectives of the study were to determine the distribution and diversity of queñoa forests in the Andean region of Tacna, Peru. With this information, We propose the restoration and conservation plan for the Polylepis spp. For this purpose plots of 500 m2 were established. The sampling was simple random, taking a population census in each of the sample units in the 4 provinces (Jorge Basadre, Tacna, Tarata and Candarave). The total evaluation area was 27,491 hectares. The presence of two Polylepis species was identified. Polylepis rugulosa Bitter was registered in 9 districts with an altitudinal range of 3050 to 4226 m.a.s.l. in 6 life zones. Polylepis tarapacana Phil is distributed in the provinces of Tarata and Tacna within 3 districts. P. tarapacana occurs in an altitudinal range between 4230 and 4750 m.a.s.l. in 5 life zones. The tall and diameter of tree were variable for two species. The human impact for P. rugulosa was recorded: Not Intervented (76%), Semi Intervening (21%) and Intervened (3%). For P. tarapacana it was: Not Intervented (77%), Semi Interventions (21%) and Intervened (2%). According to the data gathered, the conservation plan is proposed, consisting of 5 guidelines: 1) education, 2) communication and capacity building, 3) conservation and sustainable management, 4) policies and regulations, and 5) research and monitoring.